Assessment of Public Awareness and Interest on Establishment of EGovernment in Nigeria (International Journal of Engineering and Computer Science, 2017)
This study aimed to ascertain whether the citizen interest significantly support the establishment of e-government in Nigeria. Kaduna Polytechnic was used as the case study. For a month, a cross-sectional survey was conducted in the institution having randomly selected departments from the stratified colleges of the institution. The data on agreement or disagreement from the respondents were used for assessments. The survey was carried out by the same questionnaire for all respondents. The total support or agreement to the establishment of e-government was 83.33% between the age of 25 to 68 years, with the rates of 50% and 33.33% in men and women, respectively; while the total disagreement to the establishment of e-government was 13.1% between this age range, with the rates of 6.67% and 6.43% in men and women, respectively (P